Description of the final stadium larva of Macromia calliope Ris, 1916(Odonata: Anisoptera: Macromiidae) - Xu, Qi-Han (Zootaxa, 2016)
The final stadium larva of Macromia calliope Ris is described and illustrated for the first time and diagnosed against other larvae of Chinese Macromia species on the basis of published descriptions. Among the fourteen known Chinese Macromia larvae, that of M. calliope can be separated from those of non-calliope-group species by having distinctive diamond-shaped black spots located at the outside of the base of the wing sheaths. And in five Chinese calliope-group species, the larva of M. calliope can be separated from that of M. flavocolorata by apical border of prementum not obviously projecting forwards; from that of M. septima by dorsal hook on S3 thinnest and tallest of all; from that of M. chui by a relatively smaller body; from that of M. urania by nine premental setae on each side of interior prementum, five longer ones accompanied medially by four shorter ones; and finally, from those of all other Chinese Macromia species by several distinctive large V-shaped black markings on mid-dorsum of distal abdominal segments.